Application of seismic inversion in estimating reservoir petrophysical properties: Case study of Jay field of Niger Delta - Abbey Patrick Chukwuemeka; Chukwuemeka Patrick Abbey; Adetola Sunday Oniku; Emele Uduma Okpogo; Abraham Sunu Sebastian; Yusuf Mamman Dabari (Kuwait Journal of Science)
The search for Hydrocarbon around the world especially in the frontier basins has been on the increase with the sole aim of meeting up the global demand for oil and gas supply. The conventional approach in reservoir characterization uses an extrapolation of petrophysical properties from well logs to larger volumes. This technique fails to acknowledge/ factor in the heterogeneity of a reservoir and consequently leads to errors in reservoir capacity quantification. This research work employs a deterministic seismic inversion approach in determining the petrophysical properties of each reservoir sand. First, the reservoir sand was identified from intervals of low gamma-ray value with corresponding high resistivity log value. A synthetic seismogram was generated to tie the well to the seismic data and identify events that correspond to the reservoir sands. This was done by convolving the generated reflectivity series, derived from approximated Zeoppritz reflectivity with a zero-phase wavelet generated using the seismic. Acoustic impedance from the well and seismic were analyzed and proved to have a strong correlation. The impedance was then constrained with determined petrophysical parameters from the well, and it was used in generating the petrophysics base model used in the inversion. Deterministic seismic inversion was carried out to be able to determine the petrophysical properties such as porosity, the volume of shale, and water saturation that are associated with the fluids from the seismic volume of Jay-field shallow offshore of Niger Delta.